Sarcoid dactylitis: A case report of rare presentation of uncommon disease, sarcoidosis—From Ethiopia - Zerihun Gelashe Hailu; Bemnet Taye Gebregiorgis; Moges Zenebe Wegayehu; Becky Abdisa Adugna; Abdulhamid Mustefa Bedewi (Radiology Case Reports, 2024)
We present a rare case of sarcoid dactylitis after an adult female presented with painless swelling of the bilateral hand fingers and toe, with radiographic findings highly characteristic for osseous sarcoidosis and confirmation made by bronchoscopic biopsy of hilar enlarged lymph nodes.